2019
DOI: 10.1038/s41598-019-40034-6
|View full text |Cite
|
Sign up to set email alerts
|

On the emerging relationship between the stratospheric Quasi-Biennial oscillation and the Madden-Julian oscillation

Abstract: A strong relationship between the quasi-biennial oscillation (QBO) of equatorial stratospheric winds and the amplitude of the Madden-Julian oscillation (MJO) during the boreal winter has recently been uncovered using observational data from the mid-1970s to the present. When the QBO is in its easterly phase in the lower stratosphere, it favors stronger MJO activity during boreal winter, while the MJO tends to be weaker during the westerly phase of the QBO. Here we show using reconstructed indices of the MJO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
85
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 55 publications
7
85
2
Order By: Relevance
“…Using reconstructions of QBO and MJO indices back to 1905, Klotzbach et al (2019) showed that the observed QBO-MJO relationship has only emerged since the 1980s. They suggest that this emergence may be driven by the recent warming trend in the upper troposphere and cooling trend in the lower stratosphere, which together act to further reduce the stability in the equatorial tropopause, thus making the MJO more active in EQBO winter.…”
Section: Introductionmentioning
confidence: 99%
“…Using reconstructions of QBO and MJO indices back to 1905, Klotzbach et al (2019) showed that the observed QBO-MJO relationship has only emerged since the 1980s. They suggest that this emergence may be driven by the recent warming trend in the upper troposphere and cooling trend in the lower stratosphere, which together act to further reduce the stability in the equatorial tropopause, thus making the MJO more active in EQBO winter.…”
Section: Introductionmentioning
confidence: 99%
“…The strength of the MJO can be influenced by the QBO, and thus the MJO-related teleconnection changes in QBO easterly and westerly years [29]. The MJO tends to be stronger in the easterly wind phase of the QBO (QBOE) than the westerly wind phase of the QBO (QBOW), which may be attributed to the change in the static stability at the tropopause caused by the [31][32][33]. The QBO can be linked to the stratospheric polar vortex through upward propagation of planetary waves and the interaction between the stratospheric zonal mean zonal wind and the planetary waves [27].…”
mentioning
confidence: 99%
“…It is noteworthy that the QBO influences the breakdown of stratospheric polar vortices during the winter and that the polar vortex in the stratosphere, affects surface weather patterns [27]. [29] goes further to argue that when the QBO is easterly (QBOE) or negative phase in the lower stratosphere, stronger Madden Julian Oscillation (MJO) activity is likely during the northern hemisphere winter. This relationship they argue has become more evident since the 1980s when a cooling trend in the equatorial lower stratosphere and a warming trend in the equatorial upper troposphere became more evident.…”
Section: The Quasi-biennial Oscillation (Qbo)mentioning
confidence: 98%